Zinc oxide nanoparticles improve lactation and metabolism in dairy goats by modulating the rumen microbiota - Xie, Shan; Ying, Zaixiang; Xiu, Ziqing; Sun, Yawang; Yang, Qinlin; Gao, Hanyu; Fan, Wenqiao; Wu, Yongjiang (Frontiers in Microbiology, 2024)
This study aimed to investigate the effects of dietary supplementation with zinc oxide nanoparticles (ZnONPs) on lactation, rumen microbiota, and metabolomics in dairy goats. Twenty Guanzhong dairy goats, with comparable milk yields and in the mid-lactation stage, were randomly divided into two groups, with 10 goats in each group. The control group was fed a standard diet, while the ZnONP group received the control diet plus 30 mg ZnONPs/kg DM. The pre-trial period lasted for 7 days, followed by a trial period of 30 days. The results showed that the addition of ZnONPs increased the milk yield and milk fat content (p < 0.05). The results of rumen microbial sequencing showed that the Chao1, Observed species, and PD_whole_tree indices of the ZnONP group were higher than those of the control group. The addition of ZnONPs altered the composition of the rumen microbiota, increasing the abundance of beneficial bacteria (Prevotella and Rikenellaceae_RC9_gut_group) and decreasing the abundance of the harmful bacterium Sediminispirochaeta. Non-targeted metabolomics analysis identified a total of 261 differential metabolites between the two groups, indicating changes in rumen metabolism. Further correlation analysis revealed a positive correlation between beneficial bacteria (Rikenellaceae RC9 gut group and Anaeroplasma) and metabolites such as nicotinamide riboside, inosine, and guanosine (p < 0.05). In addition, a positive correlation was observed between milk yield and beneficial bacteria (RF39 and Clostridia vadinBB60 group), as well as between milk fat content and Quinella (p < 0.05). In summary, ZnONP supplementation can improve the structure of the rumen microbiota in dairy goats, positively influencing milk yield, milk composition, and metabolism.